Defect-controlled electrocaloric effect in PbZrO3 thin films. Issue 38 (13th September 2018) - Wu, Ming; Song, Dongsheng; Vats, Gaurav; Ning, Shoucong; Guo, Mengyao; Zhang, Dawei; Xue, Deqing; Pennycook, Stephen J; Lou, Xiaojie
Abstract : The structure and elemental distribution of PbZrO3 thin films are investigated. Defect controlled electrocaloric effects are discussed. Abstract : The present work demonstrates ferroelectric to antiferroelectric transition aided electric field control of positive and negative electrocaloric effects (ECE). In this context, epitaxial PbZrO3 (PZO) thin films were grown on (111) Nb:SrTiO3 single crystal substrates by the sol–gel method, and the epitaxial growth was confirmed by atomic resolution scanning transmission electron microscopy (STEM) high angle annular dark field (HAADF) images. The structural and elemental analysis revealed a gradual increase of natural lead volatilization from the middle to the top in PZO thin films. The electrocaloric effect (ECE) was calculated using Maxwell equations corresponding to 10 kHz and 100 Hz P – E data and was found to be −10.5 K (negative ECE) at 375 K and 30 K (positive ECE) at 300 K. Intriguingly, both negative and positive ECE were found in the same phase transition sequence, that is, from an antiferroelectric phase to a ferroelectric phase. The frequency dependence of ECE is found to be dependent on the polarization switching dynamics and kinetics. These results are not only scientifically important for providing an easy way to combine the negative and positive ECE together to further enhance the cooling efficiency but are also technically important for future ECE devices.